Serum Vitamin D Level in Oral Lichen Planus Patients of North India- A Case-Control Study. - Akanksha Gupta; Ravi Prakash Sasankoti Mohan; Nagaraju Kamarthi; Sangeeta Malik; Sumit Goel; Swati Gupta (Journal of Dermatologic Research And Therapy, 2017)
Background: Studies have unveiled lower levels of serum vitamin D in autoimmune diseases and the role of vitamin D in inhibition of helper T cells proliferation, stimulation of regulatory T cells, diminishing of B-lymphocyte differentiation and inhibition of immunoglobulin secretion has been discussed in the literature. Oral lichen planus (OLP) is an autoimmune mucocutaneous disorder in which cell mediated immunity plays an important part and so it may also be related to serum vitamin D levels. Aim: To estimate serum vitamin D in oral lichen planus patients of North India, compare it to the controls and to evaluate various factors influencing vitamin D level in OLP cases such as sun exposure, gender, psychosocial factors, meteorological influences, religion and diet. Methods and Material: Venous blood samples of 102 clinically diagnosed oral lichen planus patients and 102 age and sex matched controls were obtained for the study and serum vitamin D levels were estimated using Vitek Immunodiagnostic Assay System, an automated bench-top immuno-analyzer, based on the Enzyme Linked Fluorescent Assay. The data was analyzed using chi-squared test and t-test. Results: Mean vitamin D in OLP cases and controls was 20.40 ng/ml and 32.67 ng/ml respectively. Vitamin D3 deficiency was more in OLP cases (70.6%) as compared to controls (34.3%) and insufficiency was more in controls (35.3%) as compared to OLP cases (16.7%). These differences were statistically significant. Conclusion: Although vitamin D deficiency was found more in OLP cases pointing towards the possible co-relation of vitamin D and OLP, yet insufficiency was seen more commonly in controls which revealed that this important vitamin was lacking in North Indian population.
Keywords: Lichen planus